Book Review: Egyptology in the Present: Experiential and Experimental Methods in Archaeology by C. Graves-Brown (Ed) - Stephanie J. Harris (EXARC Journal)
The eye-catching and colourful cover illustration of the Egyptian creator-God Ptah, fully-equipped with modern toolkit, promises an informative journey into experiential and experimental archaeology in Egyptology. In the introductory chapter to a collection of papers presented at a conference in 2010, Graves-Brown provides a good overview and definitions of the two approaches, clearing up many controversial misconceptions. Succeeding chapters can be broadly categorized into a number of diverse topics covering woodworking, stone preparation, embalming, textiles and painting materials. The overviews of pioneering experimental work provide a sound basis for some of the other chapters.